Beberapa Faktor Resiko pada Pasien dengan Infeksi oleh E. coli dan K. pneumoniae Penghasil ESBL di RSUP H. Adam Malik Medan - Agnes, Selastri; L, Ricke; Muzahar, Muzahar (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction : Identification of risk factors for ESBL-producing bacteria infection are very important to avoidspread of ESBL and to decreased mortality. The aim of this study is to identify risk factors for infection ESBL-producing E. coli or K. pneumoniae.Method : An analytical study with cross sectional approach was conducted at H. Adam Malik hospital Medan from January-March 2014. Samples were divided into 2 groups of pairs: ESBL (n = 27) and nonESBL (n = 27). The length of hospital stay, utilization of invasive medical devices, comorbid disease, and surgery procedure are the risk factors that being analyzed. Antibiotic sensitivity tests in both groups also evaluated.Results: Based on the statistical analysis we found that the risk factors that have a significant relationship with ESBL infection was duration of hospital stay > 1 week OR 8.594 (1.680-43.953) p value 0.004, the use of peripheral venous catheters OR 0.156 (0,045-0,539) p value 0.002, urinary catheters OR 0.116 (0.023-0.595) p value 0.004, mechanical ventilator OR 0.091 (0.011-0.793) p value 0.002, nasogastric tube OR 0.160 (0.31-0.831) p value 0.018 and comorbid disease OR 15.625 (3.067-79.594). There was no significant correlation in utilization of CVC and surgery procedure. The ESBL-producing Escherichia coli or Klebsiella pneumoniae showed very good susceptibility to meropenem, imipenem (92.6%) and amikacin(85.2%).Conclusions: Risk factors associated with ESBL infections are duration of hospital stay > 1 week, the use of of invasive medical devices (peripheral venous catheters, urinary catheters, nasogastric tube and mechanical ventilator) and comorbid disease. Carbapenem is still an option for ESBL infectionKeywords : extended spectrum Î²-lactamase; risk factor; E. coli; K. pneumoniae